Planning method of logistics-distribution processes in function of distribution chains - Babić, Darko; Ivaković Babić, Morana; Průša, Petr (Univerzita Pardubice, 2009)
The logistic activities represent an optimized response to the globalization processes, and the companies involved in such activities, with optimal planning of the logistic and distribution processes, realize higher profit and more stable position on the world market. Therefore, it is necessary to define the logistic and distribution processes, their elements and interrelations, effects, as well as planning process methods, and all this in order to optimize the operation of logistic operators. Logistic-distribution processes are very complex, i.e. they consist of a multitude of details that occur in reality, but cannot influence the planning. Precisely therefore it is necessary to solve the real problems by simplified copies of these problems, the so-called models, as the basis for making a plan. The presentation of the real problem, the simplest possible but with all the necessary details and not ignoring several serious real factors, is called modelling (“art of model creation”). The basic aim of planning the logistic and distribution processes is to achieve the uniformity and consistency i.e. continuity of the goods flows and the best possible usage of the traffic infrastructure and the transport means. The above analysis of observation and research of logistics-distribution systems and its elements show that it is not possible to define the exact methods that could be applied in all cases, ie in the business of every company, so as to completely solve the problems that occur in logistic and distribution systems . Namely, different companies have different basic logistic and distribution priorities, regardless of what they all do business together in the logistic and distribution system. So as a result of the study lists a method that may be applicable in most cases, as a function of distribution channels, whose function is important in all businesses from the logistics sector.
Keywords: logistics-distribution processes; distribution chains; planning methods